Optimization of plastic mould conformal cooling for increasing production rate of plastic product [electronic resource] - Ahmad Hazlan Hasmi, 1982-; Khidzir Zakaria (2013)
Thesis (Sarjana Kejuruteraan (Mekanikal - Teknologi Pembuatan Termaju)) - Universiti Teknologi Malaysia, 2013